ANALISIS PEMBAYARAN DIVIDEN SEBAGAI INDIKATOR KUALITAS LABA (Studi Empiris Pada Perusahaan Industri Manufaktur Yang Terdaftar Di Bursa Efek Indonesia 2012 – 2016) - Indah Puspita; Herry Laksito (Diponegoro Journal of Accounting, 2019)
This study aims to examine whether the reported earnings of dividend-paying firms have high quality. There are four dividend features that is used for this study: dividend-paying status, dividend size, dividend increase, and dividend persistence. This quantitative research take the manufacturing companies listed on the Indonesia Stock Exchange in 2012-2016. Purposive sampling method is used to select the sample. It results 75 sample of companies per year. The data is obtained from financial statement that can be accessed through the IDX (Indonesia Stock Exchange). Multiple regression is used to analyze the hypotheses. All dividends feature (dividend paying status, dividend size, dividend increase, and dividend persistence) have significant relationship with earnings quality. This study used an accrual quality model as a proxy to measure earnings quality. Lower residual values from the model indicate higher earnings quality.